New Epitopes for the Serodiagnosis of Human Borreliosis - Mônica E. T. Alcón-Chino; Virgínia L. N. Bonoldi; Rosa M. R. Pereira; Gilberto S. Gazeta; João P. R. S. Carvalho; Paloma Napoleão-Pêgo; Andressa M. Durans; André L. A. Souza; Salvatore G. De-Simone (Microorganisms)
Lyme disease, a zoonotic infection caused by the bacterium Borrelia burgdorferi, is transmitted to humans through the bites of infected ticks. Its diagnosis primarily relies on serological methods; however, the existing borreliosis techniques have shown a variable sensitivity and specificity. Our study aimed to map IgG epitopes from five outer membrane proteins (Omp) from B. burgdorferi [Filament flagellar 41kD (PI1089), flagellar hook-associated protein (Q44767), Flagellar hook k2 protein (O51173), Putative Omp BURGA03 (Q44849), and 31 kDa OspA (P0CL66)] lipoprotein to find specific epitopes for the development of accurate diagnosis methods. Using the spot synthesis technique, a library of 380 peptides was constructed to identify linear B cell epitopes recognized by human IgG in response to specific B. burgdorferi-associated proteins. The reactivity of this epitope when chemically synthesized was then evaluated using ELISA with a panel of the patient’s sera. Cross-reactivity was assessed through data bank access and in vitro analysis. Among the 19 epitopes identified, four were selected for further investigation based on their signal intensity, secondary structure, and peptide matching. Validation was performed using ELISA, and ROC curve analysis demonstrated a sensitivity of ≥85.71%, specificity of ≥92.31, accuracy of ≥90.7, and AUC value of ≥0.91 for all peptides. Our cross-reactivity analysis demonstrated that the Burg/02/huG, Burg/03/huG, and Burg/12/huG peptides were not reactive to antibodies from patients with Leptospirosis and syphilis compared to those from the B. burgdorferi group. These peptides indicated an excellent performance in distinguishing between B. burgdorferi-infected and non-infected individuals and exhibited a neglected reactivity to antibodies in sera from patients with Leptospirosis and syphilis. These peptides are promising targets for recombinant development, potentially leading to more accurate serological tests and vaccines.